Automatic generation of computer models through the integration of production systems design software tools - Dias, Luís M. S. (2010)
The design of production and logistic systems is a process of managing both technical and organizational variants in order to identify the best solution for a given system. This is a very well-known industrial engineering issue, where the objectives for designing such a system have been changing over the last decades. Former approaches were concerned about material handling costs only but more recent works include re-layout and product mix costs, together with a great concern on processes – high service levels, optimal scheduling policies, setup times and costs, etc. Nowadays, the rapid technological progress and the associated competitive problems lead to a great need of fast and successful solutions to deal with continuous change (re-design) of the currently used industrial systems. Flexibility, modularity, efficiency and robustness are generally highly desired system properties. For general design of industrial systems, three basic types of software tools are used: Computer Aided Design, Simulation and Information Systems. These tools help on improving the utilization of system resources like equipment, manpower, materials, space, energy, information, etc. Nevertheless these three types of software tools have been used with low levels of integration. This absence of an adequate data connection and integration of outputs cause time delays in the design process, duplication of work and could also be a source of errors. In this work, Production Systems Design software tools integration possibilities are discussed and a unified system architecture solution, implemented on AutoCAD (layout design), Witness (Simulation) and MS-Access (Information Systems) is presented. The aim is to focus on the need of data coherence between different software tools, exploring ways of dealing with data diversity and assuring valid and efficient solutions. MS-Access supports the specification of the system and data exchange between Witness and AutoCAD. Based on the database specification, our application automatically generates simulation programs and also different spatial patterns of project layouts. These tasks are implemented in Visual Basic code. Iteratively the results from the simulations are used to improve AutoCAD layouts and AutoCAD layouts are used in new simulations. The use of our application, in the examples showed in this paper, proved to get quick, valid and efficient solutions.